Forced Marriage Prevailing in Pakistan: An Introduction and Shari'ah Analysis - Abzahir Khan; Muhammad Adeel (Journal of Islamic and Religious Studies, 2016)
The Islamic Jurisprudence has given a great importance to the existence of family system of life. That is why the Qur‘ān has described the laws of family life with details in comparison with worship of Allah. In family system of life, marriage has a great importance but marriage is not only essential part of worship. Its purposes one the existence   of human generation along with the survival society where there must be modesty and justice but it is only possible if the family system of life is established on everlasting principles. That is why our Islamic Jurisprudence has declared the willingness of both bridegroom and bride and their family more importance in the marriages. Such marriages are always durable and permanent. On the contrary, if there is no willingness of both the bridegroom and bride in marriages. Then such marriages are not durable and permanent. In marriage a girl is a party and the Islamic jurisprudence has given a great deal of importance to her willingness but in pusthoon society, sometimes such marriages are conducted in which the bride concerned has no approval rather she is forced to accept that bond of marriage such marriages are commonly called “Forced Marriages”. The article below is defining the different kinds of forced marriages in vogue and is trying to find out their religious and dogmatic status as well.